What is the middle term of the product of (x - 4)(x - 3)

Question

Asked 1/6/2015 11:26:34 AM

Updated 1/6/2015 8:49:22 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [1/6/2015 8:49:02 PM]

6x - 12 = 4;

6x = 4 + 12;

6x = 16;

x = 16/6;

x = 8/3

Shanaaz1986|Points 480|

migzptz|Points 7632|

pritilixious|Points 238|

jeifunk|Points 39812|

asero1010|Points 4484|

= -a^2 -4a + 3a + 12

= -a^2 - a + 12

Question

Asked 1/6/2015 11:26:34 AM

Updated 1/6/2015 8:49:22 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [1/6/2015 8:49:02 PM]

Rating

3

x^2 - 5x - 14

= x^2 - 7x + 2x - 7*2

= (x - 7)(x + 2)

= x^2 - 7x + 2x - 7*2

= (x - 7)(x + 2)

Added 1/6/2015 8:41:37 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/6/2015 9:48:13 PM]

3

(x - 4)(x - 3)

= x*x - 4x - 3x + 3*4

= x^2 - 7x + 12

= x*x - 4x - 3x + 3*4

= x^2 - 7x + 12

Added 1/6/2015 8:42:47 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/6/2015 9:48:39 PM]

3

a^2 - a - 20

= a*a - 5a + 4a - 5*4

= (a - 5)(a + 4)

= a*a - 5a + 4a - 5*4

= (a - 5)(a + 4)

Added 1/6/2015 8:44:07 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/6/2015 9:49:06 PM]

3

(n - 8)(n + 2)

= n^2 - 8n + 2n - 16

= n^2 - 6n - 16

= n^2 - 8n + 2n - 16

= n^2 - 6n - 16

Added 1/6/2015 8:49:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/6/2015 9:49:30 PM]

29,991,876

questions answered

There are no comments.